KERJA SAMA UNITED NATIONS CHILDREN’S FUND (UNICEF) DENGAN CENTER FOR INDONESIAN MEDICAL STUDENT’S ACTIVITIES (CIMSA) DALAM MENGKAMPANYEKAN ISU KESEHATAN MENTAL DI INDONESIA - Laily Ramadhani; Yessi Olivia (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
ABSTRACT This research will analyze the role of international organizations, namely UNICEF (United Nations International Children's Emergency Fund) in helping its member countries where the case study raised is Mental Health, world countries have followed the international framework set by the World Health Organizations (WHO) to guide world countries in Adolescent mental health. This study uses a qualitative methods, using data collection techniques through literature study which originates from a number of literature and sources related to the problem under study. This research uses the perspective of liberalism and theory using international organizations and NGOs. In tackling mental health, WHO is working with UNICEF. In 2020 UNICEF invites CIMSA In dealing with mental health in adolescents, UNICEF is working with CIMSA to find empowering ways to provide support. during Covid-19, namely with a discussion room namely PEKA (Care for Mental Health). PEKA room holds online sessions with a certain theme every 2 weeks to provide mental health and psychosocial support from and for young people. Keywords: UNICEF, CIMSA, Mental Health